An Unusual Presentation of Fronto-Ethmoidal Mucocele - Neupane, Y; Pradhan, B; Khanal, S (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: Fronto-ethmoidal mucocele; endoscopic; marsupializationDOI: 10.3126/njenthns.v1i1.4735 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.24-26